Interacting Effect Openness To Experience And Perception Of Organizational Politics On Workplace Deviant Behaviour - Dwi Hastuti; Idris Mohd Noor; Abdullah Osman; Zulkarnain Lubis (Universitas Negeri Padang, 2017)
This study investigated the interaction effect between openness to experience (one of the personality traits) and perception of organizational politics on workplace deviant behaviour. This research was conducted by collecting 263 responses from the civil servants in Pekanbaru, Riau. Applying the latest PLS 3.0 analysis tools the results of this research identified a positive correlation between openness to experience and perception of organization politics to workplace deviant behaviour. The hypothesis of interaction effect is not supported, but the result got the opposite one.